2020
DOI: 10.1007/s10123-020-00141-1
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and in vitro antifungal susceptibility of Candida albicans and Candida catenulata from laying hens

Abstract: In spite of evidence that domestic and wild birds may act as carriers of human pathogenic fungi, data on the role of laying hens as reservoirs of drug resistant and virulent yeasts is lacking. Here, we assess several virulence factors (phospholipase and haemolysin activity) and the antifungal susceptibility profiles of 84 Candida albicans and 17 Candida catenulata strains isolated from cloacae (group A), faeces (group B) and eggs (group C) of laying hens. Of these strains, 95% C. albicans and 23% C. catenulata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…D. catenulata animal isolates produce and secrete potent hydrolases (e.g., proteases and phospholipases), as previously shown by Brilhante et al [ 19 ] and Rhimi et al [ 43 ]. These enzymes are considered as virulence factors, which play fundamental roles in the pathogenesis of yeast infections [ 44 ].…”
Section: Discussionmentioning
confidence: 57%
“…D. catenulata animal isolates produce and secrete potent hydrolases (e.g., proteases and phospholipases), as previously shown by Brilhante et al [ 19 ] and Rhimi et al [ 43 ]. These enzymes are considered as virulence factors, which play fundamental roles in the pathogenesis of yeast infections [ 44 ].…”
Section: Discussionmentioning
confidence: 57%
“…A total of 68 strains isolated from the cloaca of domestic and wild animals or from the skin of hospitalized human patients with M. furfur fungemia were employed for antifungal testing ( Table 5 ). The strains were identified biochemically and molecularly, as previously reported [ 55 ]. All strains were obtained from the fungal collection of the Department of Veterinary Medicine at the University of Bari Aldo Moro, Italy.…”
Section: Methodsmentioning
confidence: 99%
“…The nuclear ribosomal ITS region was ampli ed using ITS1 (5'-TCCGTAGGTGAACCTGCGG-3') and ITS4 (5'-TCCTCCGCTTATTGATATGC-3') primers (REF). The PCR reaction consisted of 4 µl genomic DNA 100 ng and 46 µl of PCR mix containing 2.5 mM MgCl 2 , 10 mM Tris-HCl (pH8.3) and 50 mM KCl, 250 µM of each dNTP, 100 pmol of each primer and 1.25 U of AmpliTaq Gold (Applied Biosystems, Foster City, CA, USA), and run PCR protocol previously described [9]. PCR products were examined on a 2% agarose gel stained with GelRed (VWR International PBI, Milano, Italy) and visualised on a Gel Logic 100 gel documentation system (Kodak, New York, USA).…”
Section: Molecular Identi Cationmentioning
confidence: 99%
“…For example, C. albicans has been isolated from gut, cloaca and bird droppings of domestic (i.e., laying hens, broiler chickens, pigeons) and wild birds (rhea, psittacinae, raptors, cockatiels) [8]. Besides Candida, other yeast genera such as Cryptococcus, Geotrichum, Rhodotorula and Trichosporon were also isolated from environments, avian sources, and eggs [5,9], with a high number of yeasts species showing azole resistance phenomena, mainly from wild and domestic birds [9,10]. However, it has been shown that the occurrence of different fungal species and their antifungal susceptibility pro les varied accordingly with animal species and geographical area [8,11].…”
Section: Introductionmentioning
confidence: 99%